Improving Sound Absorption Property of Polyurethane Foams by Adding Tea-Leaf Fibers - KENTLİ, AYKUT; EKİCİ, BÜLENT; KÜÇÜK, HALUK (POLSKA AKAD NAUK, POLISH ACAD SCIENCES, INST FUNDAMENTAL TECH RES PAS, 2012)
The sound absorption property of polyurethane (PU) foams loaded with natural tea-leaf fibers and luffa cylindrica (LC) has been studied. The results show a significant improvement in the sound absorption property parallel to an increase in the amount of tea-leaf fibers (TLF). Using luffa-cylindrica as a filler material improves sound absorption properties of soft foam at all frequency ranges. Moreover, an increase in the thickness of the sample resulted in an improvement of the sound absorption property. It is pleasing to see that adding tea-leaf fibers and luffa-cylindrica to the polyurethane foam demonstrate a significant contribution to sound absorption properties of the material and it encourages using environmental friendly products as sound absorption material in further studies.
Keywords: fibers; polymer-matrix composites; sound absorption; tea-leaf; luffa-cylindrica; MECHANICAL-PROPERTIES; COMPOSITE FOAM